2019
DOI: 10.1103/physrevb.100.184502
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of crystal structures and superconductivity of ternary YSH6 and LaSH6 at high pressures

Abstract: We have performed a systematic study on the crystal structures and electronic properties of two ternary hydrides, YSH 6 and LaSH 6 , under pressure, using the particle swarm optimization method and first-principles calculations. As a result of extensive structure searches, metallic YSH 6 and LaSH 6 are thermodynamically stable between 195-237 and 170-300 GPa, respectively. Interestingly, in YSH 6 eight neighboring hydrogen atoms form octagons, and the octagons in different layers are connected by four sulfur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 50 publications
(90 reference statements)
2
20
0
Order By: Relevance
“…Even though a set of flat bands can be spotted near the Fermi level as well as the presence of van Hove singularities (vHs) within H 3 S 13 , YH 6 and YH 10 14 systems, leading to the possibility of achieving high values of , this can be alternatively explained by the shape of the electronic band structure or density of states of our system. Our system’s electronic structures are similar to those found in YSH 6 15 , LaSH 6 15 , CeH 9 16 , and CeH 10 19 , in terms of steep branches near the Fermi level. However, we found that Li 5 MoH 11 does not exhibit high-temperature superconductivity.…”
Section: Resultssupporting
confidence: 75%
“…Even though a set of flat bands can be spotted near the Fermi level as well as the presence of van Hove singularities (vHs) within H 3 S 13 , YH 6 and YH 10 14 systems, leading to the possibility of achieving high values of , this can be alternatively explained by the shape of the electronic band structure or density of states of our system. Our system’s electronic structures are similar to those found in YSH 6 15 , LaSH 6 15 , CeH 9 16 , and CeH 10 19 , in terms of steep branches near the Fermi level. However, we found that Li 5 MoH 11 does not exhibit high-temperature superconductivity.…”
Section: Resultssupporting
confidence: 75%
“…The CALYPSO code 32,33 based on the particle swarm optimization (PSO) method has been successfully applied to a variety of binary 7,8,34 and ternary [34][35][36] hydrides at high pressure. Herein, variable-cell crystalline structure predictions for PbH 4 , PbH 6 and PbH 8 containing 1 to 4 formula units per cell at 150 and 300 GPa were performed using the CALYPSO code.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the diversity of ternary hydrides, the difficulty in searching for new superconducting hydrides has increased exponentially, and only about 20 potential superconducting hydrides have been predicted. [ 1–21 ] Compared with binary superconducting hydrides, ternary superconducting hydrides have a higher competitive possibility to achieve the room temperature superconductivity. The successful prediction of room temperature superconductor Li 2 MgH 16 is a good demonstration (estimated value of Tc0.33em473$T_\mathrm{c}\approx \ 473$ K at 250 GPa).…”
Section: Introductionmentioning
confidence: 99%